The Econometrics of Production of Bulk Oil and Lipid Extracted Algae in an Agroindustrial Biorefinery - Roso, Gabriela R.; dos Santos, Alberto Meireles; Queiroz, Maria Isabel; Barin, Juliano Smanioto; Zepka, Leila Queiroz; Jacob-Lopes, Eduardo (Current Biotechnology, 2015)
Background: This article highlights the techno-economic analysis of a simulated large-scale process to produce bulk oil and lipid extracted algae (LEA) in an agroindustrial biorefinery. Methods: The process is based on a heterotrophic microalgal bioreactor used to simultaneously convert organic matter, nitrogen and phosphorus of the slaughterhouse wastewater into microalgal biomass. The experimental data, obtained from a bench-scale facility, were used to estimate the costs of an industrial scale (16,000 m3/day). Results: The microalgal biorefinery has capacity to produce 503,677.70 tons of biomass per year resulting in a bulk oil and lipid extracted algae production of 77,611.10 and 425,859.5 tons/year, respectively. The economic analysis foresees an estimated cost of USD 386.5 per ton of bulk oil and USD 70.4 per ton of LEA. Conclusion: The proposed technological route was demonstrated to be potentially technical and economical in providing feedstocks to energy and feed industries.
Keywords: Animal feed